PRIVATE UNIVERSITIES’ STRATEGY IN ESTABLISHING COMPETITIVE ADVANTAGES - Muzaqi, Mohamad Khanif (Proceeding of International Conference on Islamic Education (ICIED); Vol 2 No 1 (2017): Proceeding of International Conference on Islamic Education (ICIED), 2017)
This research was conducted on private universities in Malang city, East Java Indonesia, which had competitive advantages in various components, especially according to the standard assessment as stipulated in the law issued by the Ministry of Research, Technology and Higher Education no. 44 / 2015. This research was focused on the implementation and control of University Strategy to obtain competitive advantages. It also aimed to analyze the implementation of University strategy in reaching its competitive advantages. The applied theoretical basis refers to the five fundamental factors in the competition (Porter 1993); (1) the coming of new institutions, such as college, institutes; (2) the threat of substitution product (it was replaced by foreign universities looking for market in Indonesia); (3) Suppliers’ bargaining power (school bargaining power; (4) buyers’ bargaining power, (college-graduates users’ bargaining power; (5) the competition among competition participants, (big universities in Malang city). Research Method was applied in accordance with some steps as follows: (1) the conducting of field observation to private university campuses in Malang); (2) the preparing of informants, materials; (3) the conducting of interviews with the parties required by the research (rectorate officials, faculty officers, department officials / institutions in universities, students, college users; (4) the conducting of truth triangulation of epic data from some interviewee; (5) the conducting of data analysis of research data. The results of the research showed the findings that: (1) universities in Malang city have performed good governance according to the rules of the Ministry of Research, Technology and Higher Education; (2) they have different advantages according to the typical characteristics; (3) they have taken progress towards international universities; (4) they seek to create good resources, Islamic ethics and Indonesian culture.